2006
DOI: 10.2325/jbcs.13.232
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical evaluation for hormone receptors in Breast Cancer: A practically useful evaluation system and handling protocol

Abstract: This article reviews the current status of hormone receptor evaluation in and out of Japan, and introduces the proposed working protocol of the task force for Adequate immunohistochemical evaluation in routine practice for breast cancer by the Japanese Breast Cancer Society. Understanding the principles and the developmental process of immunohistochemistry helps us to utilize a scoring system adequately. Methodologies of hormone receptor examination and immunohistochemical procedures are briefly introduced. Ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
62
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(62 citation statements)
references
References 12 publications
0
62
0
Order By: Relevance
“…Mammography, ultrasound, and MRI form the backbone of breast imaging (3)(4)(5)(6). 18 F-FDG PET has also assumed an important role in wholebody staging, recurrent disease detection, and therapy response monitoring (7). Molecular breast imaging with 18 F-FDG positron emission mammography and 99m Tc-sestamibi are also being explored (3,8,9).…”
mentioning
confidence: 99%
“…Mammography, ultrasound, and MRI form the backbone of breast imaging (3)(4)(5)(6). 18 F-FDG PET has also assumed an important role in wholebody staging, recurrent disease detection, and therapy response monitoring (7). Molecular breast imaging with 18 F-FDG positron emission mammography and 99m Tc-sestamibi are also being explored (3,8,9).…”
mentioning
confidence: 99%
“…A simplified Allred score groups 0and 2; 3 and 4; 5 and 6; and 7 and 8 for 4 possible values. [7] Proportion score (PS) The most frequent tumor grade was grade I (49%) followed by grade III (40%) and grade II (11%) ( Table 3). The result of the study showed 45.16% cases were ER+/PR+, 4.84% cases ER+/PR-, 6.45% ER-/PR+ and 43.55% cases were ER-/PR-( Table 4,5,6) .…”
Section: Methodsmentioning
confidence: 99%
“…the site for evaluation was not limited to the invasive area, but incorporated the entire lesion. two scoring systems were used to evaluate the IHC findings, the Allred score (21) and J-score (2,3,22). the J-score comprises proportional values irrespective of the intensity of stained nuclei, and the proportion of cells stained in each specimen was recorded as 0, none; 1, <1%; 2, 1-10%; 3, ≥10%, as advocated and employed as the cut-off points in previous reports (23,24).…”
Section: Methodsmentioning
confidence: 99%